AI Applications for Improving Transportation and Logistics Operations - Shrikaa Jadiga, Amrish Solanki (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Transformative advancements in the enormous transportation and logistics industry are made possible by artificial intelligence (AI). Transportation businesses are achieving previously unheard-of efficiency, dependability, and strategic planning thanks to machine learning methods like deep reinforcement learning, optimization, simulation, and predictive modeling. This study examines practical AI applications in many important areas of contemporary supply chain management. It starts by reviewing how demand forecasting is enhanced by supervised and unsupervised learning algorithms that automatically analyze intricate relationships across various data sets. The use of sophisticated modeling by AI routing and scheduling algorithms to improve delivery routes down to the individual truck level based on millions of variable changes is then examined. The next section of the report covers newly developed autonomous technologies, such as robotic warehouse automation to expedite inventory management and self-driving vehicles that open up additional delivery capacity. Data and concrete use examples demonstrating AI's efficacy for transportation metrics, such as fuel savings and accident reduction, are provided for each capability. But to fully use AI, businesses must make a concentrated effort to change their processes and people to instill data-centric, analytical decision-making as a cultural norm. In general, AI is prepared to assist transportation executives in meeting the world's expanding delivery needs with previously unheard-of levels of intelligence, speed, and efficiency for the cutting-edge supply chains of the future.